One hat or many? A comparison of two models for the Copyright Officer position in university libraries - Carson, Louise; Greenhill, Kathryn (CILIP Library & Information Research Group, 2015)
Statute law provides university libraries with a framework for copyright requirements, duties and privileges. In Australia, there are few guidelines or standards for university libraries about providing those copyright services that are not mandated by statute, such as copyright advice and compliance. There is little formally-shared knowledge about the non-statutory services provided by university library Copyright Officers. More information about this would benefit libraries reviewing or establishing these positions. This research uses survey and semi-structured face-to-face interviews with designated Copyright Officers in four Western Australian universities to document four aspects of their work. These four factors are interaction and support within the library and the institution; involvement in institutional copyright advice, involvement in institutional copyright compliance; and satisfaction with authority and resourcing. The survey and interviews revealed two different models for structuring the library Copyright Officer position; one model involving a part-time officer with responsibility only for copyright, and the other model involving a full-time officer who has only 5% of their duties involved in copyright with the remainder of the copyright duties being managed by a member of the university legal / governance office. Similarities were found between the activities of both models, such as the strategies involved in ensuring copyright compliance, and education and training sessions. There was agreement from all respondents that copyright compliance within their institution could be improved by an increase in the resources available to each position.